THE APPLICATION FOR CREATING ASSIGNMENT AND ESSAY TEST FORMS FOR GENERAL ENGLISH COURSES AT SAI GON UNIVERSITY - Tuyen, THK (Proceeding of the International Conference on Arts and Humanities, 2023)
Since the Covid-19 pandemic happened globally, Viet Nam has been severely affected in all aspects, especially in the economy and education. Therefore, digital transformation and the application of modern science and technology to all activities in Vietnam are inevitable. Due to the limitation of articles, our topic will only discuss "The application to creating assignments and essay test forms for General English courses at Sai Gon University" to help lecturers and students to be more adaptable to new challenging situations in Vietnam during the period of modern technological transformation. In this article, we use the method of listing, describing and synthesizing techniques and tricks in teaching in the modern era of science and technology, specifically, the application to crofting assignments and essay test forms for General English courses via on the Moodle system at Sai Gon University. The content of the article contributes to creating not only the assignments and other tests for students, but a healthy learning environment, meeting the output standards prescribed by the Ministry of Education and Training in the integration period of Vietnam. And then, we draw concludeerve as a reference and support for lecturers and researchers in Vietnam education during the science and technology transformation period.